Hubungan Perilaku Kesehatan Ibu dengan Kejadian Diare pada Balita di Kecamatan Sungai Sembilan Kota Dumai Provinsi Riau - Wira Wasistha, Sherien Sakina; Nanda, Meutia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Sungai Sembilan sub-district holds the highest rank in cases of diarrhea in Dumai City in the last 2 years. The purpose of this study was to determine the relationship between maternal health behavior and the incidence of diarrhea in toddlers in Sungai Sembilan District, Dumai City, Riau Province. This type of research is quantitative with a cross sectional approach. The population in this study were all mothers who had toddlers with a history of diarrhea in Sungai Sembilan District, Dumai City, Riau Province. The sample taken was 100 people who were obtained using a purposive sampling technique. The data obtained in this study were processed using the chi-square test statistic. Based on the results , it was found that there was a significant relationship between mother's knowledge and the incidence of diarrhea in toddlers (p = 0.006), there was a significant relationship between mother's attitude and the incidence of diarrhea in toddlers (p = 0.013), there was no significant relationship between hand washing habits mothers with the incidence of diarrhea in toddlers (p = 0.229) and there is a significant relationship between the hygiene of mother's eating and drinking utensils and the incidence of diarrhea in toddlers (p = 0.027) in Sungai Sembilan District, Dumai City, Riau Province. Based on the research's results, the suggestions and benefits obtained are 1) can add insight into related knowledge 2) health promotion is needed in the form of routine counseling to mothers , 3) can be an additional reference in further research. Keywords: Mother’s Health Behavior; Diarrhea; Toddlers